1429Impact of BRCA mutation status and lifestyle factors on survival among women with ovarian cancer. (2nd September 2021) - Gersekowski, Kate; Jordan, Susan; Delahunty, Rachel; Alsop, Kathryn; Goode, Ellen L; Bowtell, David; DeFazio, Anna; Friedlander, Michael; Obermair, Andreas; Grant, Peter; ,
Abstract: Background: Despite their increased risk of developing ovarian cancer, women with an inherited BRCA 1 or BRCA 2 mutation have been shown to have better survival after diagnosis. Components of a healthy lifestyle, including smoking, physical activity and body mass index (BMI) have previously been associated with ovarian cancer survival; however, it is unknown whether these associations differ by BRCA mutation status. Methods: We investigated this in 2 cohorts of Australian women with invasive epithelial ovarian cancer, using Cox proportional hazards regression models to calculate adjusted hazard ratios (HRs) and 95% confidence intervals (CIs). Results: In analyses of the combined studies (n = 1, 741), the association between pre-diagnosis current smoking and poorer survival was stronger for BRCA -positive (HR 2.27; 95% CI 1.31-3.93) than BRCA -negative (HR 1.20; 95% CI 0.96-1.50) women (p-interaction 0.01). The associations between physical activity, BMI, alcohol intake and survival did not differ statistically significantly by BRCA status. A similar differential association with smoking was seen in a third independent cohort (n = 1, 009) from the USA (HR 1.93 [0.78-4.82] vs. 1.02 [0.71-1.46]). Conclusions: Our results suggest the association between smoking and survival may differ by BRCA status and that while smoking cessation may improve outcomes for all women diagnosed with ovarian cancer, it might provide a greater benefit among those who carry a BRCA mutation. Key messages: The association between pre-diagnosis smoking and poorer survival after ovarian cancer diagnosis may be stronger for women who carry a BRCA mutation compared with those who don't.